Methylation and Gene Expression of and in Colorectal Cancer Tissues - Maher Jedi; Graeme P Young; Susanne K Pedersen; Erin L Symonds (Clinical Medicine Insights: Oncology, 2018)
The genes BCAT1 and IKZF1 are hypermethylated in colorectal cancer (CRC), but little is known about how this relates to gene expression. This study assessed the relationship between methylation and gene expression of BCAT1 and IKZF1 in CRC and adjacent non-neoplastic tissues. The tissues were obtained at surgery from 36 patients diagnosed with different stages of CRC (stage I n = 8, stage II n = 13, stage III n = 10, stage IV n = 5). Methylated BCAT1 and IKZF1 were detected in 92% and 72% CRC tissues, respectively, with levels independent of stage ( P  > .05). In contrast, only 31% and 3% of non-neoplastic tissues were methylated for BCAT1 and IKZF1 , respectively ( P  < .001). The IKZF1 messenger RNA (mRNA) expression was significantly lower in the cancer tissues compared with that of non-neoplastic tissues, whereas the BCAT1 mRNA levels were similar. The latter may be due to the BCAT1 polymerase chain reaction assay detecting more than 1 mRNA transcript. Further studies are warranted to establish the role of the epigenetic silencing of IKZF1 in colorectal oncogenesis.